Optimization of Police Facility Locationing - Chow, Andy H. F.; Cheung, C. Y.; Yoon, H. T. (Transportation research record, 2015)
This paper presents an application of optimization and geographic information systems techniques for deploying police facilities subject to budgetary and feasibility constraints. The objectives include minimizing the distances and maximizing the coverage of police stations over potential crime spots. Two optimization models were investigated: maximum coverage and p-median problems. The optimization was integrated with geographic spatial analysis techniques to allocate limited police resources in the Greater London Area. In addition, the optimal results were compared with existing police deployment in London. Finally, the resilience of optimal solutions was evaluated by applying them to the scenario of the terrorist attack that occurred on July 7, 2005. This study contributes to the study of urban sustainability and security.